The prevalence of mental health problems in sub-Saharan adolescents living with HIV: a systematic review. (2020) - Dessauvagie, A.S.; Jörns-Presentati, A.; Napp, A.-K.; Stein, D.J.; Jonker, D.; Breet, E.; Charles, W.; Swart, R. L.; Lahti, M.; Suliman, S.; Jansen, R.; van den Heuvel, L.L.; et al.
Abstract: Despite the progress made in HIV treatment and prevention, HIV remains a major cause of adolescent morbidity and mortality in sub-Saharan Africa. As perinatally infected children increasingly survive into adulthood, the quality of life and mental health of this population has increased in importance. This review provides a synthesis of the prevalence of mental health problems in this population and explores associated factors. A systematic database search (Medline, PsycINFO, Scopus) with an additional hand search was conducted. Peer-reviewed studies on adolescents (aged 10–19), published between 2008 and 2019, assessing mental health symptoms or psychiatric disorders, either by standardized questionnaires or by diagnostic interviews, were included. The search identified 1461 articles, of which 301 were eligible for full-text analysis. Fourteen of these, concerning HIV-positive adolescents, met the inclusion criteria and were critically appraised. Mental health problems were highly prevalent among this group, with around 25% scoring positive for any psychiatric disorder and 30–50% showing emotional or behavioral difficulties or significant psychological distress. Associated factors found by regression analysis were older age, not being in school, impaired family functioning, HIV-related stigma and bullying, and poverty. Social support and parental competence were protective factors. Mental health problems among HIV-positive adolescents are highly prevalent and should be addressed as part of regular HIV care.